High-thermal-conductivity low-stress silicone potting adhesive for photovoltaics and preparation method thereof

CN123004355APending Publication Date: 2026-10-30ZHENJIANG LAIBO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610915594.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有高导热有机硅灌封胶依靠大量氧化铝、氮化硼无机填料搭建导热通路,但高密度刚性填料极易相互接触形成连续物理交联网络,大幅提升胶体弹性模量,丧失缓冲应力能力;光伏器件内部铜基板、硅芯片、PCB、铁氧体磁芯热膨胀系数差异悬殊,温度交变下形变差会转化巨大剪切应力,进而引发界面分层、胶体微裂纹、键合线断裂、磁芯开裂等失效问题

Benefits of technology

[0014]基于以上方面,采用双层柔性硅烷包覆改性导热填料,在粉体表面构建100~300nm弹性缓冲层,有效切断刚性填料形成的连续物理交联骨架,搭配三元柔性复配硅氧烷基体与空心硅微球协同隔断填料硬接触网络,可在填料总填充量68wt%、导热系数稳定维持1.6~1.8W/(m・K)的前提下,将胶体弹性模量控制在0.4~1.2MPa,胶体热膨胀系数调控至160~190ppm/℃,大幅缩小与铜、硅、铁氧体磁芯基材的热膨胀差值,显著降低温变过程产生的剪切应力;同时粉体预先羟基钝化配合梯度剪切三段分散工艺,可将体系内5μm以上硬质团聚颗粒占比控制在2%以内,消除应力集中源,经过-40℃~125℃上千次冷热冲击后胶体无微裂纹、界面无分层、磁芯与键合线不会出现断裂失效。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004355A_ABST
    Figure CN123004355A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of organic silicon potting adhesive for photovoltaic, and particularly relates to high-heat-conducting and low-stress organic silicon potting adhesive for photovoltaic and a preparation method thereof, which is prepared by compounding component A and component B at a mass ratio of 10:1; the component A comprises the following raw materials: ultrahigh molecular weight vinyl silicone oil, long alkyl dilution silicone oil, low expansion phenyl vinyl silicone oil, alkyl density adjusting silicone oil, composite dispersant, silane intercalation modified organic montmorillonite thixotropic agent, double-layer flexible silane coated modified composite heat-conducting filler and hollow silica microspheres; the component B comprises the following raw materials: low hydrogen-containing flexible methyl hydrogen silicone oil, silane tackifier, acetylene alcohol reaction inhibitor and platinum gold catalyst with a platinum content of 5000 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic silicone potting compound technology, and particularly relates to a high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method. Background Technology

[0002] Photovoltaic inverters, microinverters, and energy storage power modules operate outdoors in a wide temperature range of -40℃ to 125℃, placing stringent requirements on silicone potting compounds for high thermal conductivity, low internal stress, and long-term weather resistance. Existing high thermal conductivity silicone potting compounds rely on a large amount of alumina and boron nitride inorganic fillers to build thermal conductivity pathways. However, these high-density rigid fillers easily come into contact with each other, forming a continuous physical cross-linked network, significantly increasing the elastic modulus of the colloid and compromising its stress-buffering capacity. Furthermore, the significant differences in thermal expansion coefficients among the copper substrate, silicon chip, PCB, and ferrite core within photovoltaic devices lead to substantial shear stress under alternating temperatures, resulting in interface delamination, microcracks in the colloid, bond wire breakage, and core cracking. Simultaneously, the hydroxyl content on the surface of inorganic powders makes them prone to hydrogen bond aggregation, forming hard stress concentration points. During thermal shock, cracks propagate rapidly along these aggregates, significantly shortening the outdoor lifespan of the devices.

[0003] Conventional solutions, such as reducing modulus and alleviating stress, often involve decreasing filler content or adding large amounts of flexible silicone oil, directly resulting in a significant decrease in thermal conductivity. High-filler systems, on the other hand, face the challenge of excessive density differences between alumina, boron nitride, and siloxane protons. This leads to filler sedimentation and delamination before storage and curing, and after curing, inconsistencies in filler content, modulus, and coefficient of thermal expansion between the upper and lower layers continuously generate interlayer stress. This further exacerbates the risk of delamination and cracking after long-term humid and heat aging. Traditional single-silane modified powders, fumed silica anti-settling systems, and one-step high-temperature curing processes cannot simultaneously balance the four core properties of thermal conductivity, low stress, anti-agglomeration, and anti-settling, making it difficult to meet the 25-year long-term outdoor reliable operation requirements of photovoltaic equipment. Summary of the Invention

[0004] In view of the aforementioned problems, and in conjunction with the first aspect of the present invention, the present invention provides a high thermal conductivity and low stress photovoltaic silicone potting compound, which is composed of component A and component B in a mass ratio of 10:1; Component A contains the following raw materials: ultra-high molecular weight vinyl silicone oil, long alkyl diluted silicone oil, low expansion phenyl vinyl silicone oil, alkyl density regulating silicone oil, composite dispersant, silane intercalation modified organomontmorillonite thixotropic agent, double-layer flexible silane coated modified composite thermally conductive filler, and hollow silica microspheres. Component B contains the following raw materials: low-hydrogen flexible methylhydrosilicone oil, silane thickener, alkynol reaction inhibitor, and platinum catalyst with a platinum content of 5000ppm. The double-layer flexible silane-coated modified composite thermally conductive filler is a three-stage spherical alumina and hexagonal boron nitride composite system, with the total filler content accounting for 68 wt% of the total mass of component A; The composite thermally conductive filler is modified with double-layer silane coating. The inner layer is low molecular weight methylhydrosilane, and the outer layer is ultra-long flexible silicone oil with a molecular weight of 80,000 to 120,000 and low vinyl content. An elastic buffer layer of 100 to 300 nm is formed on the surface of the powder. The hollow silica microspheres have a particle size of 10–20 μm and are added at a rate of 1.5–3 wt% of the total mass of component A. The silane-intercalated modified organomontmorillonite thixotropic agent is compounded with long-chain vinyl polysiloxane to form a reversible thixotropic system, with the total addition amount accounting for 1.2-2 wt% of the total mass of component A; The total amount of the composite dispersant added accounts for 0.8 to 1.2 wt% of the total mass of component A, and it is composed of vinylsiloxane grafted polyether dispersant and low molecular weight methyl silicone oil.

[0005] Preferably, the mass ratio of the tertiary spherical alumina to hexagonal boron nitride is: 45 parts of large alumina spheres with D50=8μm, 30 parts of medium alumina spheres with D50=3μm, 15 parts of micro alumina spheres with D50=0.5μm, and 10 parts of hexagonal boron nitride with a sheet diameter of 5μm.

[0006] Preferably, the ultra-high molecular weight vinyl silicone oil has a molecular weight of 150,000 and a vinyl content of 0.03–0.05 wt%. The low-expansion phenyl vinyl silicone oil has a phenyl molar ratio of 12%; The alkyl density-adjusting silicone oil is a long-chain alkyl-branched silicone oil, added at an amount of 0.5–1 wt% of the total mass of component A, to adjust the matrix density to 1.08–1.12 g / cm³. 3 .

[0007] Preferably, the mass percentage of each raw material in component B is as follows: 7 parts of low-hydrogen flexible methylhydrosilicone oil, 1.2 parts of silane tackifier, 1 part of alkynol reaction inhibitor, and 0.8 parts of platinum catalyst with a platinum content of 5000ppm.

[0008] A method for preparing a high thermal conductivity, low stress photovoltaic silicone potting compound includes four steps: thermally conductive powder pretreatment, component A preparation, component B preparation, and device potting and curing. Pretreatment steps for thermally conductive powder: Place graded alumina and boron nitride powder in anhydrous ethanol, add neutral silanol regulator and stir at room temperature for 1 hour, filter and vacuum dry at 120℃ for 2 hours to remove adsorbed water. Methylhydrosilane was atomized and sprayed in a high-speed mixer under nitrogen protection and stirred for 30 minutes to complete the first layer grafting. Then, ultra-long flexible vinyl silicone oil was atomized and sprayed, and stirred at 120℃ for 1.5 hours to form a double-layer coating. After cooling, it was passed through a 300-mesh sieve and sealed for later use.

[0009] Preferably, the preparation steps of component A are as follows: ultra-high molecular weight vinyl silicone oil, long alkyl diluted silicone oil, low expansion phenyl vinyl silicone oil, and alkyl density adjusting silicone oil are added to a room temperature reactor and stirred at 300 r / min for 10 min to mix evenly. Add the composite dispersant and silane intercalation modified organomontmorillonite thixotropic agent and stir for 20 minutes until the additives are completely dissolved; Double-layer coated composite thermally conductive filler and hollow silica microspheres were added in batches, and each batch of filler was stirred for 15 minutes to eliminate dry material clumping. Vacuumed to -0.092MPa, dispersed at a medium speed of 1200r / min for 60min, and then homogenized at a high speed of 25m / s for 20min to break up hard agglomerated particles. Cool to 30℃ and stir at low speed of 300r / min for 10min to release shear stress. Allow to stand under vacuum for 30min to defoam. Filter through a 200-mesh filter to obtain component A. Store in a light-proof, sealed container.

[0010] Preferably, the preparation steps of component B are as follows: low hydrogen content flexible methyl hydrosilicone oil, silane thickener, and alkynol reaction inhibitor are added to the reaction vessel at room temperature, and the mixture is stirred at 500 r / min for 15 min until homogeneous. A platinum catalyst with a platinum content of 5000 ppm was slowly added dropwise under a light-protected environment, and the mixture was stirred continuously for 30 minutes. After slight vacuum degassing for 10 minutes, the product is filtered through a 150-mesh filter and then stored in a light-proof, sealed container.

[0011] Preferably, the device potting and curing steps are as follows: Components A and B are statically mixed at a mass ratio of 10:1 using an automatic metering device, and the device is potted under a vacuum of -0.085MPa; after potting, the device is allowed to stand at room temperature for 15 minutes to stabilize the thixotropic network; it is then transferred to an oven for step curing, and kept at 60℃ for 40-60 minutes for low-temperature pre-crosslinking to lock in the filler distribution, and then heated to 100℃ for 120 minutes for deep crosslinking; after curing, the device is slowly cooled in the oven, with the cooling rate controlled to ≤2℃ / min, to obtain the finished product.

[0012] Preferably, after the gradient shear three-stage dispersion process, the proportion of hard agglomerates with a particle size greater than 5 μm in the system is less than 2%.

[0013] Preferably, after the potting compound is cured, the difference between the elastic modulus and the coefficient of thermal expansion between the upper and lower layers of the compound is less than 5%, the elastic modulus of the compound is controlled between 0.4 and 1.2 MPa, the overall coefficient of thermal expansion is 160 to 190 ppm / ℃, and the thermal conductivity is 1.6 to 1.8 W / (m·K).

[0014] Based on the above, a double-layer flexible silane-coated modified thermally conductive filler is used to construct a 100-300nm elastic buffer layer on the powder surface, effectively cutting off the continuous physical cross-linking skeleton formed by rigid fillers. Combined with ternary flexible composite siloxane esters and hollow silicon microspheres to synergistically isolate the hard contact network of the filler, the colloidal elastic modulus can be controlled at 0.4-1.2MPa and the colloidal thermal expansion coefficient can be adjusted to 160-190ppm / ℃, while maintaining a total filler content of 68wt% and a stable thermal conductivity of 1.6-1.8W / (m・K). This significantly reduces the thermal expansion difference with copper, silicon, and ferrite magnetic core substrates and significantly reduces the shear stress generated during temperature changes. At the same time, the pre-hydroxyl passivation of the powder combined with a gradient shear three-stage dispersion process can control the proportion of hard agglomerates larger than 5μm in the system to within 2%, eliminating stress concentration sources. After thousands of thermal shocks from -40℃ to 125℃, the colloid shows no microcracks, no interface delamination, and the magnetic core and bonding wires do not break or fail.

[0015] This invention utilizes a multi-level particle size distribution of thermally conductive fillers combined with a silane-modified montmorillonite reversible thixotropic system, supplemented by long-chain alkyl branched silicone oil to reduce the density difference between the matrix and inorganic fillers. This effectively suppresses filler sedimentation due to gravity, and the delamination thickness of the adhesive does not exceed 0.5 mm after 90 days of storage at room temperature. Combined with a 60℃ low-temperature pre-crosslinking and locking step curing process, the difference in modulus and coefficient of thermal expansion between the upper and lower layers of the cured adhesive is less than 5%, completely eliminating long-term interlayer internal stress. The entire process does not use high-tackification fumed silica, and the system viscosity is reduced by 40% compared to traditional solutions. The adhesive has excellent flowability, sufficient wetting of gaps without bubbles, and the overall formula contains no polar additives, which will not cause platinum catalyst poisoning. It balances mass production processability with 25 years of outdoor damp heat and salt spray aging stability, perfectly meeting the long-term reliable potting requirements of photovoltaic power devices. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the execution process of the high thermal conductivity and low stress photovoltaic silicone potting compound provided in the embodiments of the present invention. Detailed Implementation

[0017] The present invention will now be described in detail with reference to the accompanying drawings. Figure 1 This is a schematic diagram of the process of a high thermal conductivity, low stress photovoltaic silicone potting compound provided in one embodiment of the present invention. The following is a detailed description of the high thermal conductivity, low stress photovoltaic silicone potting compound.

[0018] A double-layer flexible silane coating process is used to treat alumina and boron nitride powders. First, the hydroxyl groups on the powder surface are passivated by grafting low molecular weight methylhydrosilane to eliminate hard hydrogen bond contacts between particles. Then, ultra-long flexible silicone oil with a molecular weight of 80,000 to 120,000 and a low vinyl content is sprayed to form an elastic buffer layer of 100-300 nm on the powder surface, cutting off the continuous physical cross-linking skeleton of rigid fillers. Under the same high filling amount, the colloidal elastic modulus can be controlled at 0.4-1.2 MPa. The matrix uses a ternary compound siloxane system, with the main component being ultra-long linear vinyl silicone oil with a molecular weight of 150,000 and a vinyl content of 0.03-0.05 wt%. The intrinsic modulus is reduced by relying on sparse chemical cross-linking points. The compounded alkyl-modified silicone oil is used as a molecular lubricating buffer phase, combined with low-expansion phenyl vinyl silicone oil with a phenyl molar ratio of 12%, to control the overall thermal expansion coefficient of the colloidal material to 160-190 ppm / ℃, reducing the deformation difference with copper, silicon, and magnetic core substrates. 1.5~3wt% of hollow silica microspheres with a particle size of 10~20μm are added to the system. The microspheres fill the gaps between the thermally conductive fillers and act as elastic isolation nodes, further breaking the rigid stacking network. The decrease in thermal conductivity is controlled within 0.15W / (m・K).

[0019] Before powder modification, an anhydrous ethanol hydroxyl passivation process is added. After adding a neutral silanol regulator and stirring at room temperature for 1 hour, the mixture is filtered and dried to reduce the free hydroxyl groups on the powder surface to below 80 ppm, thus inhibiting powder self-agglomeration from the source. The system is compounded with a total addition of 0.8~1.2 wt% of a two-component siloxane dispersant. A vinyl siloxane-grafted polyether dispersant anchors the flexible coating layer of the powder, achieving compatibility between the filler and the matrix interface. Low molecular weight methyl silicone oil wets the powder to reduce particle friction. Polar organic additives are avoided throughout the process to prevent platinum catalyst poisoning. The processing stage adopts a gradient shear three-stage dispersion process. The powder is premixed at a low speed of 300r / min for 30 minutes to fully wet the powder. The powder is dispersed at a medium speed of 1200r / min for 60 minutes under a vacuum of -0.09MPa to break up soft agglomerates and degas them. Then, the powder is homogenized at a high speed of 25m / s for 20 minutes to tear apart dense hard agglomerates. After dispersion, the proportion of hard agglomerates larger than 5μm in the system is less than 2%, eliminating stress concentration sources for crack propagation under thermal shock.

[0020] A multi-level particle size distribution of tertiary spherical alumina combined with lamellar boron nitride is employed. 8μm large spherical alumina accounts for 45% of the total filler mass, 3μm medium spherical alumina for 30%, 0.5μm micro-spherical alumina for 15%, and 5μm hexagonal boron nitride for 10%. The interlocking of large and small particles creates packing resistance, while the interlaced lamellar boron nitride forms a spatial support framework, significantly reducing the settling rate of heavy alumina. High-viscosity fumed silica is abandoned; instead, 1.2–2 wt% silane-intercalated modified organomontmorillonite combined with long-chain vinyl polysiloxane is used to construct a reversible thixotropic system. When stationary, the nanosheets form a three-dimensional support network to lock in the filler. Under stirring and shearing, the network instantly dissociates, ensuring low flowability during dispensing. The overall viscosity of the system is reduced by 40% compared to the fumed silica system without additionally increasing the colloidal modulus. The addition of 0.5–1 wt% long-chain alkyl branched silicone oil increases the siloxane bulk density to 1.08–1.12 g / cm³. 3 This process reduces the density difference between the matrix and inorganic fillers, weakening the driving force of gravity settling. The molding and curing process employs a stepped low-temperature locking process. After pouring the adhesive, it is left to stand at room temperature for 15 minutes to stabilize the thixotropic structure. Then, it is transferred to an oven at 60℃ for 40-60 minutes for low-temperature pre-crosslinking, forming a slightly crosslinked network to fix the filler distribution. Finally, the temperature is raised to 100℃ and held for 120 minutes to complete deep curing. After curing, the difference in modulus and coefficient of thermal expansion between the upper and lower layers of the adhesive is less than 5%, eliminating interlayer stress. After curing, the cooling rate is controlled to ≤2℃ / min for slow cooling in the oven to avoid instantaneous temperature stress caused by rapid cooling.

[0021] In the pretreatment stage, graded alumina and boron nitride powders are put into anhydrous ethanol for passivation and cleaning. After filtration, they are vacuum dried at 120°C for 2 hours to remove adsorbed moisture. They are then transferred to a high-speed mixer under nitrogen protection, and methylhydrosilane is sprayed and stirred for 30 minutes to complete the first layer grafting. Then, ultra-long flexible vinyl silicone oil is sprayed and stirred at 120°C for 1.5 hours to form a double-layer coating. After cooling, it is passed through a 300-mesh sieve and sealed for later use. In the preparation of component A, ultra-high molecular weight vinyl silicone oil, long alkyl diluted silicone oil, low-expansion phenyl vinyl silicone oil, and alkyl density adjusting silicone oil are sequentially added to the reactor. The mixture is stirred at 300 rpm for 10 minutes at room temperature to mix the matrix. A composite dispersant and modified montmorillonite thixotropic agent are added and stirred for 20 minutes until the additives are completely dissolved. Double-layer coated composite thermally conductive filler and hollow silica microspheres are added in batches. Each batch of filler is stirred for 15 minutes to eliminate dry material agglomeration. The vacuum is evacuated to -0.092 MPa, and the mixture is dispersed at 1200 rpm for 60 minutes to defoam and break up soft agglomerates. The mixture is then homogenized at high speed for 20 minutes to break up hard agglomerates. The temperature is lowered to 30°C and stirred at low speed for 10 minutes to release shear stress. After vacuum standing and defoaming for 30 minutes, the mixture is filtered through a 200-mesh filter, sealed, and stored in a light-proof container. Component B is prepared by adding low-hydrogen flexible methylhydrosilicone oil, silane tackifier, and alkynyl alcohol reaction inhibitor at room temperature, stirring at 500 rpm for 15 minutes to mix thoroughly, then slowly adding 5000 ppm platinum catalyst under light-protected conditions while stirring for 30 minutes. After slight vacuum degassing for 10 minutes, the mixture is filtered through a 150-mesh filter and stored in a light-protected, sealed container. The ratio of A:B is fixed at 10:1. For terminal encapsulation molding, a two-component automatic metering static mixing method is used. Vacuum encapsulation at -0.085 MPa is applied to fully impregnate the device gaps. After completion, the mixture is allowed to stand at room temperature for 15 minutes to stabilize the filler distribution. A step-by-step curing process is then performed, starting at 60℃ for pre-gelation and then at 100℃ for deep cross-linking. Finally, a controlled slow cooling rate is used to complete the product molding.

[0022] It should be noted that, in order to simplify the description of the present invention and thus help to understand one or more embodiments of the invention, multiple features may sometimes be grouped into one embodiment, drawing or description thereof in the foregoing description of the embodiments of the present invention.

[0023] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.

Claims

1. A high thermal conductivity, low stress photovoltaic silicone potting compound, characterized in that: It is a compound of component A and component B in a mass ratio of 10:1; Component A contains the following raw materials: ultra-high molecular weight vinyl silicone oil, long alkyl diluted silicone oil, low expansion phenyl vinyl silicone oil, alkyl density regulating silicone oil, composite dispersant, silane intercalation modified organomontmorillonite thixotropic agent, double-layer flexible silane coated modified composite thermally conductive filler, and hollow silica microspheres. Component B contains the following raw materials: low-hydrogen flexible methylhydrosilicone oil, silane thickener, alkynol reaction inhibitor, and platinum catalyst with a platinum content of 5000ppm. The double-layer flexible silane-coated modified composite thermally conductive filler is a three-stage spherical alumina and hexagonal boron nitride composite system, with the total filler content accounting for 68 wt% of the total mass of component A; The composite thermally conductive filler is modified with double-layer silane coating. The inner layer is low molecular weight methylhydrosilane, and the outer layer is ultra-long flexible silicone oil with a molecular weight of 80,000 to 120,000 and low vinyl content. An elastic buffer layer of 100 to 300 nm is formed on the surface of the powder. The hollow silica microspheres have a particle size of 10–20 μm and are added at a rate of 1.5–3 wt% of the total mass of component A. The silane-intercalated modified organomontmorillonite thixotropic agent is compounded with long-chain vinyl polysiloxane to form a reversible thixotropic system, with the total addition amount accounting for 1.2-2 wt% of the total mass of component A; The total amount of the composite dispersant added accounts for 0.8 to 1.2 wt% of the total mass of component A, and it is composed of vinylsiloxane grafted polyether dispersant and low molecular weight methyl silicone oil.

2. The high thermal conductivity, low stress photovoltaic silicone potting compound according to claim 1, characterized in that: The mass ratio of the tertiary spherical alumina to hexagonal boron nitride is as follows: 45 parts of large alumina spheres with D50=8μm, 30 parts of medium alumina spheres with D50=3μm, 15 parts of micro alumina spheres with D50=0.5μm, and 10 parts of hexagonal boron nitride with a sheet diameter of 5μm.

3. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 1, characterized in that: The ultra-high molecular weight vinyl silicone oil has a molecular weight of 150,000 and a vinyl content of 0.03–0.05 wt%. The low-expansion phenyl vinyl silicone oil has a phenyl molar ratio of 12%; The alkyl density-adjusting silicone oil is a long-chain alkyl-branched silicone oil, added at an amount of 0.5–1 wt% of the total mass of component A, to adjust the matrix density to 1.08–1.12 g / cm³. 3 .

4. The method for preparing a high thermal conductivity, low stress photovoltaic silicone potting compound according to claim 1, characterized in that: The mass percentage of each raw material in component B is as follows: 7 parts of low-hydrogen flexible methylhydrosilicone oil, 1.2 parts of silane tackifier, 1 part of alkynol reaction inhibitor, and 0.8 parts of platinum catalyst with a platinum content of 5000ppm.

5. A method for preparing a high thermal conductivity, low stress photovoltaic silicone potting compound, based on the high thermal conductivity, low stress photovoltaic silicone potting compound according to any one of claims 1-4, characterized in that: It includes four steps: thermally conductive powder pretreatment, component A preparation, component B preparation, and device potting and curing. Graded alumina and boron nitride powders were placed in anhydrous ethanol, and a neutral silanol regulator was added and stirred at room temperature for 1 hour. After filtration, the powders were vacuum dried at 120°C for 2 hours to remove adsorbed water. Methylhydrosilane was atomized and sprayed in a high-speed mixer under nitrogen protection and stirred for 30 minutes to complete the first layer grafting. Then, ultra-long flexible vinyl silicone oil was atomized and sprayed, and stirred at 120℃ for 1.5 hours to form a double-layer coating. After cooling, it was passed through a 300-mesh sieve and sealed for later use.

6. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 5, characterized in that: The specific steps for preparing component A are as follows: put ultra-high molecular weight vinyl silicone oil, long alkyl diluted silicone oil, low expansion phenyl vinyl silicone oil, and alkyl density adjusting silicone oil into a room temperature reactor, and stir at 300 r / min for 10 min to mix evenly. Add the composite dispersant and silane intercalation modified organomontmorillonite thixotropic agent and stir for 20 minutes until the additives are completely dissolved; Double-layer coated composite thermally conductive filler and hollow silica microspheres were added in batches, and each batch of filler was stirred for 15 minutes to eliminate dry material clumping. Vacuumed to -0.092MPa, dispersed at a medium speed of 1200r / min for 60min, and then homogenized at a high speed of 25m / s for 20min to break up hard agglomerated particles. Cool to 30℃ and stir at low speed of 300r / min for 10min to release shear stress. Allow to stand under vacuum for 30min to defoam. Filter through a 200-mesh filter to obtain component A. Store in a light-proof, sealed container.

7. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 5, characterized in that: The specific steps for preparing component B are as follows: At room temperature, add low-hydrogen flexible methyl hydrosilicone oil, silane thickener, and alkynol reaction inhibitor to the reactor and stir at 500 r / min for 15 min to mix evenly. A platinum catalyst with a platinum content of 5000 ppm was slowly added dropwise under a light-protected environment, and the mixture was stirred continuously for 30 minutes. After slight vacuum degassing for 10 minutes, the product is filtered through a 150-mesh filter and then stored in a light-proof, sealed container.

8. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 1, characterized in that: The specific steps of device potting and curing are as follows: Components A and B are statically mixed at a mass ratio of 10:1 using an automatic metering device, and the device is potted under a vacuum of -0.085MPa; after potting, the device is allowed to stand at room temperature for 15 minutes to stabilize the thixotropic network; it is then transferred to an oven for step curing, and kept at 60℃ for 40-60 minutes for low-temperature pre-crosslinking to lock in the filler distribution, and then heated to 100℃ for 120 minutes for deep crosslinking; after curing, the device is slowly cooled in the oven, with the cooling rate controlled at ≤2℃ / min, to obtain the finished product.

9. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 1, characterized in that: After the gradient shear three-stage dispersion process, the proportion of hard agglomerates with a particle size greater than 5μm in the system is less than 2%.

10. The high thermal conductivity, low stress photovoltaic silicone potting compound and its preparation method according to claim 1, characterized in that: After curing, the elastic modulus and coefficient of thermal expansion of the upper and lower layers of the potting compound deviate by less than 5%. The elastic modulus of the compound is controlled between 0.4 and 1.2 MPa, the overall coefficient of thermal expansion is 160 to 190 ppm / ℃, and the thermal conductivity is 1.6 to 1.8 W / (m·K).